The Use of Intraoperative Neurophysiological Monitoring in Spine Surgery. Issue 1 (January 2020) - Charalampidis, Anastasios; Jiang, Fan; Wilson, Jamie R. F.; Badhiwala, Jetan H.; Brodke, Darrel S.; Fehlings, Michael G.
Study Design: Narrative review. Objective: To summarize relevant studies regarding the utilization of intraoperative neurophysiological monitoring (IONM) techniques in spine surgery implemented in recent years. Methods: A literature search of the Medline database was performed. Relevant studies from all evidence levels have been included. Titles, abstracts, and reference lists of key articles were included. Results: Multimodal intraoperative neurophysiological monitoring (MIONM) has the advantage of compensating for the limitations of each individual technique and seems to be effective and accurate for detecting perioperative neurological injury during spine surgery. Conclusion: Although there are no prospective studies validating the efficacy of IONM, there is a growing body of evidence supporting its use during spinal surgery. However, the lack of validated protocols to manage intraoperative alerts highlights a critical knowledge gap. Future investigation should focus on developing treatment methodology, validating practice protocols, and synthesizing clinical guidelines.